Applying the Geneva Conventions: Military Commissions, Armed Conflict, and Al-Qaeda - Rubin, Alfred P. (Tufts Archival Research Center, 2005)
Volume 26, Issue 1. Winter/Spring President George W. Bushï¿½s executive order allowing the establishment of military commissions to try foreigners for acts of terrorism has come under severe criticism. What many have failed to realize is that a simpler solution to the problem exists.